The Effectiveness of Implementing PBL and Susan Loucks Horsley Syntax Combination with the Deep Learning Approach to Science Process Skills in Junior High School - Rosaniya E Rehiara (Postgraduate, University of Mataram, 2026)
This study aims to determine the effectiveness of the application of a combination of PBL and Susan Loucks Horsley (SLH) syntax with a deep learning approach on students' science process skills in junior high school science learning. This study used a quasi-experimental Nonequivalent Control Group design with a purposive sampling technique, where the school studied was grade VIII students of SMP Negeri 6 Sentani, Jayapura Regency. Data collection techniques were questionnaires and observation sheets. Data analysis was carried out descriptively and quantitatively, using independent sample-test, N-Gain, and effect-size tests. The results showed that the application of a combination of PBL and SLH syntax with a deep learning approach can improve students' science process skills in science learning at SMP Negeri 6 Sentani, Jayapura Regency. The results of the difference test showed a significant difference in the science process skills of students taught using a combination of PBL and SLH syntax with a deep learning approach with students taught using a conventional model. The value of the science process skills of students taught using a combination of PBL and SLH science syntax with a deep learning approach was higher than the value of students taught using a conventional model. The effectiveness of the combination of PBL and SLH syntax with the deep learning approach is in the high category based on the N-Gain value and effect-size test.